If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-30=f+-29
We move all terms to the left:
-30-(f+-29)=0
We add all the numbers together, and all the variables
-(f-29)-30=0
We get rid of parentheses
-f+29-30=0
We add all the numbers together, and all the variables
-1f-1=0
We move all terms containing f to the left, all other terms to the right
-f=1
f=1/-1
f=-1
| -9r-24-7=-1 | | r+-169=150 | | 6=(n-2)180 | | -4(2x+3)=2x+6-(8x*2) | | -62=y+-87 | | 25=16.50x | | -4(-x-1)+5x=2x+19 | | h-438=146 | | -4(-x-1)+x=2x+19 | | -21f=-840 | | 900=300h | | -24y+12=12 | | 4x2-20+25=0 | | 3x=298.17 | | 1/2(6x-3)=3-x | | q+-2=14.2 | | h=-16(9)+75(3) | | u+136=-598 | | x10=1215 | | .75(x+16)=3-0.5(x-8) | | -31q=-496 | | 245=5g | | 16z=-464 | | 47.14=2(3.14)r | | -f-8=-18 | | 12r=924 | | 6x+11=-(6x+5)+7)=6x+9-4x | | d+23=74 | | 3x-3+2×=112 | | -31q=806 | | 126=7h | | x2-20+25=0 |